Determinants of Financial and Digital Financial Literacy Among Micro and Small-Scale Enterprise Owners in Yogyakarta, Indonesia - Siwi, Virgiana Nugransih; Sasongko, Gatot; Pertiwi, Angelita Titis; Wahyudi, Yustinus; Megaleia Rosedea, Eukharistein; Andra Martian, Thomas (Industrija, 2026)
This study examines the levels and determinants of financial literacy (FL) and digital financial literacy (DFL) among micro-scale enterprise owners in Yogyakarta. Using survey data from micro enterprises across multiple sectors, the analysis assesses literacy across knowledge, attitudes, and behavioural dimensions. The findings reveal that both FL and DFL remain relatively low, particularly in knowledge and behaviour, despite generally positive attitudes. Demographic characteristics, gender, age, and education, significantly influence FL and DFL, with male, younger, and more educated owners exhibiting higher literacy. Socioeconomic factors also shape outcomes: permanent income employment decreases DFL, family income support enhances digital financial attitudes, while a larger number of dependents and reliance on community-based financial support reduce digital financial engagement. Business characteristics such as turnover and type, along with technology-related factors including internet access and digital payment tools, further affect literacy levels; however, access alone does not guarantee responsible digital financial behaviour. Mediation analysis confirms that FL plays a critical role in strengthening DFL, underscoring the importance of foundational financial knowledge and behaviour in digital financial adoption. The study offers insights for policies aimed at improving digital financial inclusion among micro enterprises in emerging economies.